Analisis Tingkat Kesehatan Bank Dengan Metode RGEC Pada Bank Umum BUMN Yang Terdaftar di Bursa Efek Indonesia Tahun 2014-2016 - I Made Laut Mertha Jaya (EBBANK, 2018)
This research is conducted to know the health level of BUMN Bank using RGEC (Risk Profile, Good Corporate Governance, Earnings, Capital) during 2014-2016. This research belongs to the type of evaluative research. This study uses secondary data. This research concludes that PT. Bank BNI, Tbk, PT. Bank BRI, Tbk, and PT. Bank Mandiri, Tbk during the Year 2014-2016 as a whole can be said that the health of the Bank is very healthy. Meanwhile, PT. Bank BTN, Tbk during the Year 2014-2016 as a whole the soundness of the Bank, which is quite healthy. This proves that the ability of the company's performance results achieved very well is inversely proportional to the health condition of the Bank. In addition, in terms of valuation of profitability factors measured using ROA and NIM ratio during the period 2014 to 2016 BTN Bank obtain less healthy category. This reflects that the company's profitability capability is inadequate, and its level of profitability has not been fully in line with the target. This low rating compared to the other three state-owned banks shows that the ability of Bank BTN in generating profit has not been maximized and need to re-evaluate the performance that has been achieved during the period 2016.